Only a Girl: or, A Physician for the Soul. - Hillern, Wilhelmine von, 1836-1916; Wister, A. L. (Annis Lee), 1830-1908 (Salt Lake City, UT : Project Gutenberg, 2011)
"Only a Girl: or, A Physician for the Soul" by Wilhelmine von Hillern is a novel written in the late 19th century. It follows the story of a delicate young girl named Ernestine Hartwich, who struggles against the harsh environment and disdainful treatment from her father and others around her due to her gender and appearance. The book explores themes of neglect, self-worth, and the quest for identity in a society that elevates boys over girls. The opening of the novel introduces us to Ernestine, a frail, neglected child living in a desolate estate in Northern Germany. Her father, a cruel invalid, expresses disappointment in her for being a girl, and their interactions are marked by conflict and emotional abuse. Ernestine's only moments of respite come from the rare kindness displayed by a stranger at a party, contrasting sharply with her home life where she feels unloved and ugly. The chapter sets the tone for Ernestine's challenging existence, her yearning for acceptance, and the deeper societal issues regarding gender perceptions and familial relationships that will unfold throughout the narrative. (This is an automatically generated summary.)
Release date is 2011-07-11
Produced by Charles Bowen, from page scans provided by the Web Archive
Keywords: German fiction -- Translations into English